MEDIA IN AN ERA OF DIGITAL GLOBALIZATION: THE ETHICAL PERSPECTIVES - GABRIEL T. NYITSE; STEPHEN WANG (International Studies Journal)
The 21st century has witnessed unparalleled digital revolution, driven by the proliferation of digital technologies, which has transformed how individuals’ access, consume, and engage with information. The internet, mobile devices, and social media platforms have connected people across the globe, creating a global digital ecosystem where information transcends physical boundaries. This digital globalization has introduced numerous benefits, including democratizing knowledge access and fostering cross-cultural understanding, but it has also raised complex ethical challenges. This text explores the complex ethical considerations that arise in the era of digital globalization. It addresses issues related to media ethics, social media use, data privacy, and the impact of legislation on digital citizenship. The Social Responsibility Theory was used as a critical framework emphasizing the need for responsible and ethical media practices in a rapidly changing landscape. One of the primary ethical concerns in the digital age is the safeguarding of individual privacy and data security. The collection, storage, and utilization of personal data by corporations, governments, and online platforms have raised significant ethical dilemmas. Additionally, the ease of information dissemination on digital platforms has led to the rapid spread of disinformation, misinformation, and fake news, challenging the ethical responsibility of individuals and organizations to verify and counter false narratives. This study concludes that, the digital age's ethical landscape is complex and multifaceted, shaped by technology, society, culture, and individual agency. Understanding and addressing these ethical challenges are crucial as societies adapt to the opportunities and complexities of digital globalization. This study thus called on individuals, organizations, policymakers, and educators to navigate the digital era with responsible and ethical practices, upholding democratic values while embracing the benefits of digital interconnectedness.